2017
DOI: 10.12659/msm.899941
|View full text |Cite
|
Sign up to set email alerts
|

Liver Injury and Tumor-Inhibiting Effect of Sequential Transcatheter Arterial Chemoembolization and Portal Venous Embolization on Rabbit VX2 Liver Carcinoma

Abstract: BackgroundThe concepts of sequential transcatheter arterial chemoembolization (TACE) and portal venous embolization (PVE) were proposed to prevent the detrimental tumor growth-inducing effect of PVE and to facilitate growth of further future liver remnant (FLR). This study aimed to investigate the effect of sequential TACE and PVE on liver damage and the therapeutic effect in a rabbit VX2 liver tumor model.Material/MethodsRabbits bearing VX2 liver tumors were randomly divided into TACE+PVE, TACE, PVE, and Sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the previous studies, the incidence rate of TACE + PVE–induced complete tumor necrosis was 80%, which was significantly higher compared with that in the treatment of TACE alone (50%) and PVE alone (5%) [ 27 , 28 ]. Animal model experiments also confirmed the distinguished efficacy [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 74%
“…In the previous studies, the incidence rate of TACE + PVE–induced complete tumor necrosis was 80%, which was significantly higher compared with that in the treatment of TACE alone (50%) and PVE alone (5%) [ 27 , 28 ]. Animal model experiments also confirmed the distinguished efficacy [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 74%
“…Previous research in a rabbit VX2 liver tumor model demonstrated that liver injury is aggravated after TACE treatment, with the significantly increased plasma ALT and AST levels ( Song et al, 2017 ). Our results are broadly consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%